Stopping the Leaks. - Savage, Neil (Communications of the ACM, 2013)
The article focuses on research into side channel vulnerability and computer security. It states that software applications can gain information about virtual machine servers and infer what other programs are doing, thus increasing the vulnerability of encryption keys and cryptographic algorithms. It mentions research that examines a virtual file of process information in the Unix operating system to determine the amount of memory is allocated to a program and determine what websites a smartphone user is visiting. It comments that malicious mobile device applications can infer telephone, credit card numbers, and social security numbers inputted onto keypads. It talks about methods of increasing security, including increasing data noise or disabling different systems.